IdentifyiIdentifying and Analyzing the Effects of Variables and Indicators Effectively on the Strategic Importance of Harirud for Iran with the Interaction Impact Analysis Approach - Morad Kaviani Rad; Afshin Mottaghi; Hadi Zarghani; Hasan Sadrania (تحقیقات کاربردی علوم جغرافیایی)
One of the problems in analyzing hydro-political relations in the system of international rivers is that the same factors can create a wide range of conflict or cooperation, and even an identical variable may play a different role in relation to other variables in each coastal country; Therefore, the recognition of the variables and the role that each variable has in developing a pattern of analysis of opportunities and risks for countries that share transboundary waters with other countries is essential. Iran is in the Harirud basin shared with Afghanistan. The presence of this basin in a dry and semi-arid strip of world has caused Iran's dependence on the water of Harirud to provide water to the east and northwest, and especially to the metropolis of Mashhad. Therefore, the research question is: What are the variables and indicators effective on the Strategic Importance of Harirud for Iran? For this purpose, 86 indicators were identified using library and field studies and categorized in geographical-geopolitical, technical-economical, and political-social variables in expert meetings with experts. After identifying the most important variables using the Delphi method, the role of each variable in the structural analysis of the variables has been investigated with the help of the Micmac software. The results indicate that geopolitical -geographical variables are the most effective and Most impressive variables, and indicators of the importance of Harirud for drinking water, food security, security of water resources and Afghanistan's position in Iran's foreign policy, strategic indicators for the importance of Heriud for Iran.